Premenstrual Syndrome on Reproductive Health of Adolescent Girls in the Baru Ladang Bambu Village, Medan Tuntungan District in 2018 - Suriati Lubis; Sari Rahma Fitri (Institute of Computer Science (IOCS), 2019)
The purpose of this study is to increase the knowledge and insight of young women about reproductive health and premenstrual syndrome, so that young women can find out how to prevent and deal with menstruation (menstruation/menstruation) to female students/adolescents in Ladang Bambu Village, Medan Tuntungan District. . And the activities Increasing the knowledge of female students/adolescents about reproductive health and premenstrual syndrome, so that young women can know how to prevent and handle menstruation (menstruation/menstruation) in Ladang Bambu Village, Medan Tuntunga District. Increasing the knowledge of young women on the prevention and treatment of premenstrual syndrome.The type and form of activity of this activity is to provide material to female students/adolescents about reproductive health and premenstrual syndrome, so that young women can know how to prevent and treat when facing menstruation (menstruation/menstruation). To achieve the objectives of the above activities, activities were carried out, among others, providing counseling on reproductive health and premenstrual syndrome, so that young women can know how to prevent and deal with menstruation (menstruation/menstruation) in Ladang Bambu Village, Medan Tuntungan District.